Extreme conditions in the shipping Noteć Leniwa (Lazy Noteć) - Nadolny, Grzegorz (Journal of Education, Health and Sport, 2018)
The practice of inland navigation and its planning is dependent on the parameters of the route navigable section of the river or canal forming part of the waterway. Information about the parameters of the data shows the corresponding local authority waterway in relation to its class. These parameters give guarantees that inland shipping can safely be done on a given stretch of the waterway, and each trip will be carried out according to the previously adopted plan. Transport of goods on the waterways and practicing water tourism requires a stable and predictable transit depth, the width of the navigable route, etc. Provision and maintenance of marine parameters, belongs to the administration of the waterway and is dependent on factors meteorological and hydrological conditions of the area. The article presents the characteristics of hydrological conditions Noteć Leniwa, based on the occurrence of extreme events. On the basis of hydrological data from 2018, defined extreme states (WW and NW) for Noteć Leniwa. They had a direct impact on the safety of navigation in relation to the parameters pathway navigable waterway as a class. The study was conducted at the Lazy Noteć section of 106 km (estuary) to 57 km (estuary Łobżonka). Field measurements were carried out in 2018. They involved bathymetric soundings (of depth) in the longitudinal profile navigable route. To determine the hydrological data used daily water levels (IMGW) of water gauge stations (Ujście, Bialosliwie), supplemented by data PGW Polish waters - Bydgoszcz Regional Board of hydraulic engineering (Krostkowo).Extreme water levels in the context of the possibility of using the route navigable both concern the situation of maximum (WW) and minimum (NW) values. Such hydrological situation has a direct impact on the safety of navigation. This was the case in 2018, subject to detailed analysis. Conclusions. On the examinations, on the impact of extreme hydrological events on the possibility of shipping Noteć Leniwa, it was found that:Fluvial processes and the lack of regular maintenance work navigable route, contribute to the systematic deterioration of the waterway.An additional difficulty in the conduct of navigation on the Noteć Leniwa, is thriving, during the growing aquatic vegetation.In areas not meeting the operating parameters required for a particular class waterway, work to be carried out dredging operation.It is also advisable to restore the function of drainage system in the valley of the Noteć Lazy, which will help to maintain the water at The operational level, regardless of the hydrological situation.In addition, for low water levels expose the flying course of the route marking and labeling navigable visual height of the lumens under bridges at high water.In contrast, the basic problem for the continuity of the navigation section of the test is to ensure that the depth of the transit regardless of the hydrological situation, which can be done only through rational management of water covering the whole basin of Noteć.